2020
DOI: 10.1021/acssensors.0c00960
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stretchable Fiber-Based Potentiometric Ion Sensors for Multichannel Real-Time Analysis of Human Sweat

Abstract: Wearable potentiometric ion sensors are attracting attention for real-time ion monitoring in biological fluids. One of the key challenges lies in keeping the analytical performances under a stretchable state. Herein, we report a highly stretchable fiber-based ion-selective electrode (ISE) prepared by coating an ion-selective membrane (ISM) on a stretchable gold fiber electrode. The fiber ISE ensures high stretchability up to 200% strain with only 2.1% increase in resistance of the fiber electrode. Owing to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 42 publications
0
60
0
Order By: Relevance
“…In contrast, sweat is easy to access noninvasively through the skin and is rich in important analytes, such as electrolytes (e.g., Na + , Cl − , K + , and pH) and metabolites (e.g., glucose, lactate, and cortisol) [ 21 , 22 ]. Recent studies have shown that potentiometric ion sensors in a wearable format are useful for real-time monitoring of dynamic changes in ion concentrations in sweat during an individual’s activities [ 23 , 24 ]. The on-body monitoring of sodium and chloride ions in sweat can be utilized to indicate dehydration status and to diagnose cystic fibrosis [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, sweat is easy to access noninvasively through the skin and is rich in important analytes, such as electrolytes (e.g., Na + , Cl − , K + , and pH) and metabolites (e.g., glucose, lactate, and cortisol) [ 21 , 22 ]. Recent studies have shown that potentiometric ion sensors in a wearable format are useful for real-time monitoring of dynamic changes in ion concentrations in sweat during an individual’s activities [ 23 , 24 ]. The on-body monitoring of sodium and chloride ions in sweat can be utilized to indicate dehydration status and to diagnose cystic fibrosis [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Potentiometric sensors are advantageous because of the simplicity of operation, low power consumption, and their potential for miniaturization [117][118][119]. Recently, wearable-type potentiometric ion sensors (WPISs) integrated with IoT sensing modules have gained significant attention for their applicability toward the real-time monitoring of ion concentration changes in body fluids for healthcare management, sports performance monitoring, and physiological analysis [120,121]. Additionally, they can be employed for the diagnosis of critical nervous disorders and heart failure by monitoring metabolic indicators such as Na + , K + , and pH [122,123].…”
Section: Ion Sensorsmentioning
confidence: 99%
“…Then, 20 µL reference membrane (RM) solution was drop-casted on the Ag/AgCl and dried overnight in ambient conditions. The RM solution was prepared by dissolving 500 mg of the membrane cocktail in 5 mL of THF: 150 mg PVC and 340 mg DOS, 5.5 mg TDMACl, 4.5 mg KTPFB, 808 mg KCl, and 306 mg AgCl powder were mixed and stirred overnight at ambient temperature [50,51]. After the RM dried, a reference protection layer was further covered on the RM.…”
Section: Preparation Of Flexible Electrodesmentioning
confidence: 99%